Hierarchy of evolution equations for correlations of hard-sphere fluids - Gapyak, I.V.; Gerasimenko, V.I. (Reports of the National Academy of Sciences of Ukraine, 2022)
In the communication we discuss an approach to describing the correlations in a system of many hard spheres based on the hierarchy of evolution equations for correlation functions. It is established that the constructed dynamics of correlations underlies the description of the dynamics of both finitely and infinitely many hardspheres governed by the BBGKY hierarchies for reduced distribution functions or reduced correlation functions.